Competition in the German interurban bus industry: A snapshot two years after liberalization - Niklas S. Dürr; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We study competition in the German interurban bus industry two years after its liberalization in January 2013. In addition to a brief characterization of the liberalization process and several general market developments, we provide a detailed analysis of selected market characteristics such as concentration and competitive interaction, fares as well as service quality. We use the gained insights to discuss two recent policy issues - industry consolidation and possible abuses of market power by incumbents - and derive several recommendations to secure effective competition in the industry.
urn:nbn:de:bsz:180-madoc-397379
Keywords: L11; L41; L43; L92; K21; K23; 330; liberalization; interurban bus services; competition; merger; predation; Germany